Radiation and porosity effects on the magnetohydrodynamic flow near a vertical plate that applies shear stress to the fluid with mass diffusion - Khan, Arshad (American Institute of Physics Inc., 2014)
This article studies the radiation and porosity effects on the unsteady magnetohydrodynamic free convection flow of an incompressible viscous fluid past an infinite vertical plate that applies a shear stress f(t) to the fluid. Conjugate phenomenon of heat and mass transfer is considered. General solutions of the dimensionless governing equations along with imposed initial and boundary conditions are determined using Laplace transform technique. The solution of velocity is presented as a sum of mechanical and non mechanical parts. These solutions satisfy all imposed initial and boundary conditions and reduce to some known solutions from the literature as special cases. The results for embedded parameters are shown graphically. Numerical results for skin friction, Nusselt number and Sherwood number are computed and presented in tabular forms.